Mechanical properties of whiskers - Артемьев, Сергей Робленович; Андронов, Владимир Анатольевич; Семкив, Олег Михайлович (Technology audit and production reserves, 2013)
It is known that the structure of thread-like crystals is perfect and the limit of their strength approaches to the theoretical. However, the studies showed the ambiguity of relationship between the structure of perfect «whiskers» and their high strength. Literature review, conducted in the paper, concerning the research of such group of properties of thread-like crystals as mechanical properties, showed the presence of defects in the crystal structure of «whiskers» and the dependence of the strength of crystals on transverse and longitudinal sizes of «whiskers». The study of mechanical properties of thread-like crystals is considered in many of literature sources, in particular 12 sources were mentioned in the paper, but evaluations of the results of experimental studies are quite different and ambiguous. Based on the literature review, corresponding conclusions on some mechanical properties of thread-like crystals were considered, estimated and outlined in the paper, the influence of the changes of their characteristics on the structure of crystals and ambiguity of estimation of direct relationship between the strength of crystal and its structure was analyzed.